Barriers to adherence of stroke rehabilitation: therapist and patient’s perspective - Taliha Hamid Tareen; Arshad Nawaz Malik; Saira Jahan (Journal of the Pakistan Medical Association, 2025)
Objective: To explore the perspectives of physiotherapists and patients regarding barriers to stroke rehabilitation. Method: The qualitative, descriptive study was conducted from January to December 2022 after approval from the ethics review board of Riphah International Hospital, Islamabad, Pakistan, and comprised sub-acute and chronic stroke patients and physiotherapists having two years of clinical experience. The sample was raised using non-probability purposive sampling technique from hospitals/clinics in Rawalpindi and Islamabad. Data was collected through semi-structured interviews. During the interviews, the patients were asked about their experiences with rehabilitation programmes and the factors affecting their rehabilitation. The therapists were asked to share their thoughts on the factors affecting the patients’ adherence to stroke rehabilitation. Data was subjected to thematic analysis using ATLAS.ti 9. Results: Of the 30 subjects, 15(50%) were patients; 13(86.6%) females and 2(13.3%) males with mean age 49.5±5.6 years and mean treatment duration 6.3±1.2 months. The remaining 15(50%) subjects were physiotherapists; 13(86.6%) females and 2(13.3%) males, with 8(53.3%) having three years of experience. Four themes were identified from the data related to the physiotherapists: experience and requirements of stroke rehabilitation, barriers to adherence of stroke rehabilitation, suggestions to improve stroke-rehabilitation, and avoiding non-adherence, motivational factors. Also, four themes were identified from the data related to the patients: experience and quality of life after stroke, major and minor barriers in stroke rehabilitation, positive and negative aspects of rehabilitation, and suggestions and factors to enhance participation in rehabilitation programmes. Conclusion: Multiple patient-related barriers regarding adherence to rehabilitation were noted, including social and physical barriers and financial issues, while therapist-related barriers included time management issues and poor stroke rehabilitation infrastructure. Key Words: Adherence, Patients, Physiotherapists, Rehabilitation, Stroke.